Evaluation of confirmatory data following the Article 12 MRL review and setting of an import tolerance for flutriafol in cucurbits (inedible peel). (7th December 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: The applicant Cheminova A/S submitted a request to the competent national authority in the United Kingdom to evaluate the confirmatory data for the active substance flutriafol that were identified in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005. The applicant provided residue trials on rice representative for an adjusted Good Agricultural Practice (GAP), metabolism studies in goats and storage stability data in tissues of animal origin addressing the data gaps identified in the MRL review. For the nature of residues in processed commodities, relevant to confirm the MRLs on pome fruits and wine grapes, the applicant referred to the information provided in a previous MRL application and already assessed by EFSA. The data gaps on the authorised uses on beetroots, melons and watermelons assessed in the MRL review were not addressed. At the same time, the applicant submitted a request to the United Kingdom to modify the existing maximum residue level (MRL) for flutriafol in cucurbits with inedible peel according to Article 6 of Regulation (EC) No 396/2005. The data submitted were found to be sufficient to derive an MRL proposal for these crops. EFSA concluded that the proposed use of flutriafol on the crops under assessment will not result in a consumer exposure exceeding the toxicological reference values for flutriafol and therefore is unlikely to pose a risk to consumers' health. Regarding the triazole derivative metabolites (TDMs), the conclusions reached in a previously issued assessment for another triazole fungicide are still valid. An update of the indicative consumer risk assessment for each individual metabolite is not necessary since the residues expected in the concerned commodities are covered.